Stand der Verkehrstelematik in Deutschland im Europavergleich. - Groke, Roland; Zackor, Heinz (Deutscher Verkehrs-Verl., 2004)
Moderne Verkehrstechnik nutzt die Möglichkeiten moderner Informations- und Kommunikationstechnologien (Telematik), die weitgehend in internationalem Maßstab entwickelt werden. Wo stehen wir in Deutschland mit Forschung und Entwicklung sowie Umsetzung in die Praxis im europäischen Vergleich? difu

Modern traffic engineering uses the potentialities of modern information and communication technology, widely developed at international scale. In terms of implementation the situation is indifferent, also depending on the mode of transport. Main barriers opposing a harmonised implementation of telematics have an institutional and organisational, respectively a legal and regulative character, especially in the co-operation of public and private actors. Moreover, at present there are hardly any consistent information and control strategies for a targeted use of telematics. What is the position of Germany in research and development and in implementation in relation to the other European countries? difu
Keywords: Verkehr; Ablauf; Verkehrstechnik; Informationstechnologie; Untersuchung; Straßenverkehr; Schienenverkehr; Fernverkehr; ÖPNV; Binnenschiffsverkehr; Seeschiffsverkehr; Luftverkehr; Informationstechnologie; Verkehrstelematik; Infrastrukturnutzung; Ländervergleich